2021
DOI: 10.1186/s11671-021-03559-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Bone Marrow Mesenchymal Stem Cell-Derived Exosomal MicroRNA-133a Restrains Myocardial Fibrosis and Epithelial–Mesenchymal Transition in Viral Myocarditis Rats Through Suppressing MAML1

Abstract: Myocarditis is a disease characterized by localized or diffuse inflammation of the myocardium without efficient treatment. This study explored the regulatory mechanism of microRNA-133 (miR-133) secreted from bone marrow mesenchymal stem cell-derived exosome (BMSC-Exo) on myocardial fibrosis and epithelial–mesenchymal transition (EMT) in viral myocarditis (VMC) rats through regulating mastermind-like 1 (MAML1). BMSCs in rats were isolated and cultured to identify their immune phenotype and osteogenic and adipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The BMSCs were extracted as previously described [ 26 ]. Briefly, Wistar rats (approximately 50 g) were sacrificed by CO 2 inhalation and soaked in 75% alcohol for about 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The BMSCs were extracted as previously described [ 26 ]. Briefly, Wistar rats (approximately 50 g) were sacrificed by CO 2 inhalation and soaked in 75% alcohol for about 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The group treated with exosomal miR-133a showed lower levels of inflammatory factors than other groups. Noteworthily, the highest levels of these cytokines were observed in the miR-133a-silenced rats [54]. Liu et al showed that miR-21 and miR-146b levels were significantly higher in mice presenting with VMC than in healthy individuals.…”
Section: Intervention In Viral Myocarditis In Vivo Models-other Analy...mentioning
confidence: 99%
“…In rats, overexpression of miR-133a BMSC-Exos ameliorates Coxsackie B3 virus-induced viral myocarditis (VMC), which causes shaggy hair, dyspnea, poor diet, body weight loss, improved LVPW and LVID and decreased LVEF and FS, and the inhibition of miR-133a expression limited this effect (Li et al, 2021b). The target of miR-133a was located on MAML1, and the upregulation of miR-133a inhibited the expression of MAML1 (Li et al, 2021b).…”
Section: Exosomes That Alter the Expression Of Specific Genesmentioning
confidence: 99%
“…In rats, overexpression of miR-133a BMSC-Exos ameliorates Coxsackie B3 virus-induced viral myocarditis (VMC), which causes shaggy hair, dyspnea, poor diet, body weight loss, improved LVPW and LVID and decreased LVEF and FS, and the inhibition of miR-133a expression limited this effect (Li et al, 2021b). The target of miR-133a was located on MAML1, and the upregulation of miR-133a inhibited the expression of MAML1 (Li et al, 2021b). After si-MAML1 treatment, VMC rats gained weight, improved cardiac function, attenuated myocardial histopathology and fibrosis and inhibited the serum inflammatory response and apoptosis of cardiomyocytes (Li et al, 2021b).…”
Section: Exosomes That Alter the Expression Of Specific Genesmentioning
confidence: 99%